The effect of obesity, weight gain, and weight loss on asthma inception and control - Forno, Erick (Curr Opin Allergy Clin Immunol, 2017)
PURPOSE OF THE REVIEW: There is ample and growing evidence that obesity increases the risk of asthma and morbidity from asthma. Here we review recent clinical evidence supporting a causal link between obesity and asthma, and the mechanisms that may lead to “obese asthma”. RECENT FINDINGS: While in some children obesity and asthma simply co-occur, those with “obese asthma” have increased asthma severity, lower quality of life, and reduced medication response. Underlying mechanistic pathways may include anatomical changes of the airways such as obstruction and dysanapsis; systemic inflammation; production of adipokines; impaired glucose-insulin metabolism; altered nutrient levels; genetic and epigenetic changes; and alterations in the airway and/or gut microbiome. A few small studies have shown that weight loss interventions may lead to improvements in asthma outcomes, but thus far research on therapeutic interventions for these children has been limited. SUMMARY: Obesity increases the risk of asthma –and worsens asthma severity or control– via multiple mechanisms. “Obese asthma” is a complex, multifactorial phenotype in children. Obesity and its complications must be managed as part of the treatment of asthma in obese children.